LINGUISTIC FACTORS IN CHANGING MEANING OF IDIOMATIC COMPOUNDS IN ENGLISH AND UZBEK LANGUAGES - Odinaxon TEMIROVA, (TADQIQOTLAR, 2026)
Annotation This  article  explores  the  linguistic  factors  that  contribute  to  changes  in  the meanings  of  idiomatic  compounds  in  English  and  Uzbek  languages.  Idiomatic compounds  —  fixed  multi-word  expressions  whose  overall  meaning  cannot  be deduced from the meanings of individual components — are deeply rooted in cultural and historical contexts. The research focuses on semantic shifts, influence of cultural contact,  translation  challenges,  and  cognitive  motivations  behind  idiom  evolution. Drawing on comparative analysis, the paper examines how social changes, language contact, metaphorical extensions, and communicative needs affect idiomatic usage and interpretation in both languages. It highlights key differences and similarities between English and Uzbek idioms, reflecting distinct cultural values, worldview patterns, and linguistic structures. Additionally, the study discusses how globalization and increased bilingualism  influence  idiomatic  transformation.  The  findings  show  that  semantic adaptation often involves metaphorical reconceptualization, pragmatic reanalysis, and idiom borrowing or calquing. This article contributes to cross-linguistic idiom studies and provides insights for translators, language teachers, and computational linguists dealing  with  natural  language  understanding.  The  comparative  framework demonstrates that while some idiomatic changes are universal, others are language-specific, driven by sociocultural dynamics.